PROFIL PEDAGANG KAKI LIMA YANG MENGGUNAKAN BILKO (MOBIL TOKO) DI JALAN CUT NYAK DIEN KOTA PEKANBARU - ", Renta; ", Syafrizal (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
The existence of street vendors who use a car shop on the one hand is needed by consumers, especially employees of government offices located around the Cut Nyak Dien, but on the other hand its existence actually disturbing the peace, cleanliness and comfort of the user community. In accordance with local regulations on public order, the city government taken any action against street vendors. Traders will be pursuing a strategy to keep them survive selling along Jalan Cut Nyak Dien. Results of the study showed that the trader chose to stick with a reason to meet the economic needs of the family and the location of Cut Nyak Dien is a promising market for street vendors. The reason that makes traders have a strategy to survive in order to keep selling by ridding the area of selling, Ask for the Protection and Defense of Pekanbaru City Council, Sell and Preserving unique culinary Riau, Strengthening Social Solidarity between the Fellow Street Vendors, cat and mouse with the municipal police officers. Besides traders have a strategy to maintain their business from the competition by building relationships with buyers, competition in taste, and set the time to sell. The purpose of this study is also to analyze the merchant profile. To determine the total number of merchants and determine informants used in the field study using purposive sampling method. The data field of the overall number of traders who use the Car Shop amounted to 15 merchants by taking as many as 8 research subjects merchant. To collect data from informants used the method of direct observation, interview and documentation, for processing the data used qualitative methods. The results showed that the traders from West Sumatra, 36-60 years old, have a secondary education, high school and undergraduate, length of stay in Singapore is generally more than 15 years and monthly income ranges between 5 million rupiahs.Keywords: Profile, Street Vendors, And Strategies Survive